Optimization of yogurt production using demineralized whey - Penna, Ana Lucia B. [UNESP]; Baruffaldi, Renato; Oliveira, Maricê N. (Wiley, 1997)
The effect of three independent fermentation variables: demineralized whey powder (0.0; 1.5 and 3.0%), lactic culture concentration (1.0; 2.0 and 3.0%) and mix treatment temperature (85; 90 and 95°C) was studied. Fermentation time to reach pH 4.3, instrumental consistency and appearance, visual consistency and taste of the product were evaluated. Product consistency increased as mix treatment temperature increased and demineralized whey powder decreased. The powder had a stronger influence on instrumental consistency than did temperature. Appearance was better when whey powder was used at 1.4 to 1.6%. Visual consistency decreased as whey powder increased but addition of demineralized whey powder did not negatively affect yogurt flavor.
Keywords: Demineralized whey; Fermentation; Lactic acid; Sensory; Yogurt; demineralization; fermentation; whey